Photoshop CC the missing manual - Snider, Lesa (O'Reilly Media, 2014)
Annotation
Online resource; title from title page (Safari, viewed August 29, 2014)
Keywords: Adobe Photoshop; Image processing -- Digital techniques; Traitement d'images; Techniques numériques; digital imaging; Image processing; Digital techniques